2022
DOI: 10.1377/hlthaff.2021.01428
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Police Encounters, Health, And Violence In A Southern City

Abstract: The disproportionate rates of police surveillance and encounters in many communities in the US may be contributing to inequities in health and violence. Frequent policing in communities, which may often also be aggressive policing, has been associated with diminished health and well-being. This study adds to the growing body of research on this issue by examining the relationships between neighborhood police stop-and-frisk encounters and both health outcomes and violence rates in New Orleans, Louisiana, in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The limited availability of data existent to test our theoretical model meant that in our empirical model we were restricted by measures capturing constructs that directly result from, but are operationally different from, structural racism. Recent studies in the US have empirically documented the association between structural racism and health inequities using individual exposure measures like police encounters (Theall et al, 2022) and racialised disenfranchisement (Homan & Brown, 2022), or multidimensional measures of structural racism developed using latent variable models (Chantarat et al, 2021). Although we didn't have access to similar constructs, measures we had available at the institutional-level such as inequities in socioeconomic position, area-level deprivation, and household overcrowding, are clear outcomes of structural and institutional racism.…”
Section: Discussionmentioning
confidence: 99%
“…The limited availability of data existent to test our theoretical model meant that in our empirical model we were restricted by measures capturing constructs that directly result from, but are operationally different from, structural racism. Recent studies in the US have empirically documented the association between structural racism and health inequities using individual exposure measures like police encounters (Theall et al, 2022) and racialised disenfranchisement (Homan & Brown, 2022), or multidimensional measures of structural racism developed using latent variable models (Chantarat et al, 2021). Although we didn't have access to similar constructs, measures we had available at the institutional-level such as inequities in socioeconomic position, area-level deprivation, and household overcrowding, are clear outcomes of structural and institutional racism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the adverse effects of police experiences can spillover onto the adjustment of people as an aggregate among adult-aged samples. For instance, neighborhood-level police stops have predicted elevated psychological distress (Sewell et al, 2016) and diminished health among neighborhood adult-aged residents (Sewell et al, 2021; Sewell & Jefferson, 2016; Theall et al, 2022). Similarly, police-perpetrated killings have deleterious repercussions for Black adults’ mental health (Bor et al, 2018; Curtis et al, 2021).…”
Section: The Spillover Effects Of Police Intrusion On Adolescents’ Sc...mentioning
confidence: 99%
“…Both direct and vicarious exposure to police use of deadly force have been linked to poor health outcomes, most notably poor mental health . Even exposure to nonlethal police encounters have been linked to poor health outcomes . Sleep health may be adversely affected through several of the mechanisms identified in this literature.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35] Even exposure to nonlethal police encounters have been linked to poor health outcomes. [36][37][38] Sleep health may be adversely affected through several of the mechanisms identified in this literature. Officer-involved killings may diminish expectations about future well-being and longevity, induce hypervigilance, and increase stress including posttraumatic stress disorder, many of which have been associated with poor sleep.…”
mentioning
confidence: 97%